KEMAMPUAN SPASIAL SISWA DITINJAU DARI TAHAPAN BERPIKIR VAN HIELE DI SMP NEGERI 1 BANDUNG TULUNGAGUNG - Agzistasari, Anggun; Zahroh, Umy; Maryono, Maryono (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
The objectives of this study were (1) to describe the spatial abilities of students using the Van Hiele thinking stages, (2) to find out the differences in students' spatial abilities in terms of the Van Hiele thinking stages based on the Van Hiele level groups. The method used is a mixed method type design, sequential explanatory with qualitative research followed by quantitative research first. Qualitative data collection techniques using observation, tests, and interviews with the subject of 6 students. Quantitative data collection technique with a sample obtained of 64 students using a test, by testing the hypothesis using the one way ANOVA test. The results of this study are as follows (1) Students' spatial abilities in terms of the Van Hiele thinking stage level 0 (Visualization) only meet the indicator spatial ability, namely spatial visualization, at the Van Hiele thinking stage level 1 (Analysis) meets the spatial ability indicators, namely spatial visualization and mental rotation. at the Van Hiele thinking stage level level 2 (informal deduction) fulfills all spatial ability indicators, namely spatial visualization, spatial perception and mental rotation, (2) There are differences in students' spatial abilities in terms of Van Hiele thinking stages based on group level 0 (Visualization), level 1 (Analysis), and level 2 (Informal Deduction).